Sobre o poder germinativo de sementes do algodao mocó, Gossypium hirsutum Marie-Galante Hutch., tratadas pelo ácido sulfúrico - Ponte, J. Julio Da (Instituto Interamericano de Ciencias Agrícolas (IICA), 2025)
The germinative power of Macó cotton seeds (Gossypium hirsutum mariegalante Hutch) desinfected with concentrated sulphuric acid (density 184) during 50 minutes of exposition, was determined sowing the seeds at 1, 15, 30 and 45 days from the date of desinfection. The not desinfected seeds showed, in every phase of the experiment, a smaller percentage of germination. The seeds treated with acid and sown one day after the treatment showed a percentage of germination that dif-fered statistically from that observed in the seeds des-infected and sown 45 days after the desinfection. Such an ocurrence cannot be explained as a noxious effect of the acid over stored seeds, since the same result was observed in the controls in relation with every stage.